2008
DOI: 10.1111/j.1469-0691.2007.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of type III secretion system virulence among fluoroquinolone-susceptible and -resistant clinical isolates of Pseudomonas aeruginosa

Abstract: Fluoroquinolone resistance and type III secretion system (TTSS) virulence are independently associated in Pseudomonas aeruginosa infections with poor patient outcomes. In the present study, the virulence of fluoroquinolone-susceptible and -resistant isolates of P. aeruginosa was compared, focusing on TTSS virulence. Clinical isolates (n = 45) exhibiting a broad range of susceptibilities to fluoroquinolones, with differing mechanisms of resistance and associated with varying disease sites, were selected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 40 publications
(68 reference statements)
11
68
3
2
Order By: Relevance
“…The prevalence of exoU was 62.4% in all examined P. aeruginosa isolates which was third in prevalence to exoT and exoY in the T3SS genotypes of isolates tested, contrasting with a number of studies 11,12,18 that reported exoU prevalence to be the lower one in P. aeruginosa isolates compared to the other secretion toxins genes. It was stated that exoU gene was acquired via horizontal transmission on a plasmid, and then integrated in the P. aeruginosa genome.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The prevalence of exoU was 62.4% in all examined P. aeruginosa isolates which was third in prevalence to exoT and exoY in the T3SS genotypes of isolates tested, contrasting with a number of studies 11,12,18 that reported exoU prevalence to be the lower one in P. aeruginosa isolates compared to the other secretion toxins genes. It was stated that exoU gene was acquired via horizontal transmission on a plasmid, and then integrated in the P. aeruginosa genome.…”
Section: Discussioncontrasting
confidence: 83%
“…7,10 Deletion of exoU severely limits the toxicity of P. aeruginosa strain in lung, and the enzyme has been implicated as an agent associated with septic shock and increased disease severity and mortality in pneumonia. 7,11 Interestingly, the genes encoding P. aeruginosa T3SS toxins are found in some isolates but not in others. 12 The distribution of these genes among isolates of P. aeruginosa and the frequency in populations of isolates from different disease sites has not been thoroughly examined in our country…”
mentioning
confidence: 99%
“…All ExoU isolates were MDR, which is consistent with Mitov et al [30], who found a higher frequency of MDR among ExoU isolates compared with ExoS isolates. Consistent with the current finding regarding the high prevalence of fluoroquinolone resistance in ExoU isolates (100%), Wong-Beringer et al [38] found that 92% of ExoU were fluoroquinolone-resistant compared with 61% resistance in ExoS. The association between MDR and the presence of the ExoU genotype has been associated with poor clinical outcome in patients with pneumonia in two different studies, particularly in immunocomporomised patients [39,40], with no clear genetic explanation.…”
Section: Figsupporting
confidence: 73%
“…Some published studies have reported that exoU-positive P. aeruginosa strains are most often multi-resistant compared with exoS strains (Garey et al, 2008;Wong-Beringer et al, 2008). In our study, this relationship was not observed as the strains with the TTSS genotype were also multiresistant, suggesting again that these bacteria could exhibit other additional resistance mechanisms that make these strains present multiple antimicrobial co-resistance.…”
Section: Discussioncontrasting
confidence: 58%